2003
DOI: 10.1007/s00431-003-1179-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic illness, life style and emotional health in adolescence: results of a cross-sectional survey on the health of 15-20-year-olds in Switzerland

Abstract: experimental behaviours are not rarer in adolescents with a chronic condition and might be explained by a need to test their limits both in terms of consumption and behaviour. Prevention and specific attention from the health caring team is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 34 publications
7
68
0
4
Order By: Relevance
“…Por otro lado, investigaciones en muestras de adolescentes, representativas de realidades nacionales, revelan prevalencias de vida de intentos suicidas que varían entre 1,5% y 12,1% y prevalencias de 12 meses de 1,8% a 8,4% [6][7][8] . Además, en ese grupo etario se han encontrado prevalencias de vida de ideas suicidas que fluctúan entre 21,7% y 37,9%, y de planes suicidas de 3,0%; y prevalencia de 12 meses de 26,0% para ideas suicidas y 15,0% para planes suicidas 6,8,9 . Chile no dispone de tasas de prevalencia de intentos ni de ideas suicidas en la población general a nivel nacional.…”
unclassified
“…Por otro lado, investigaciones en muestras de adolescentes, representativas de realidades nacionales, revelan prevalencias de vida de intentos suicidas que varían entre 1,5% y 12,1% y prevalencias de 12 meses de 1,8% a 8,4% [6][7][8] . Además, en ese grupo etario se han encontrado prevalencias de vida de ideas suicidas que fluctúan entre 21,7% y 37,9%, y de planes suicidas de 3,0%; y prevalencia de 12 meses de 26,0% para ideas suicidas y 15,0% para planes suicidas 6,8,9 . Chile no dispone de tasas de prevalencia de intentos ni de ideas suicidas en la población general a nivel nacional.…”
unclassified
“…But, contradicting somehow other studies that have found significant differences in substance consumption or risky behaviour in adolescents with and without chronic conditions (Miauton et al, 2003;Blum et al, 2001;The McCreary Centre Society, 1993), chronic disease is not associated with more frequent consumption of tobacco or alcohol. This may be accounted by differences in the definition of chronic conditions, here referring only to somatic diseases, while in other studies sensory, motor or learning disabilities were included.…”
Section: Discussionmentioning
confidence: 60%
“…Also, there has been a greater awareness of the special health needs of these youngsters that go further than adaptation to the special life conditions imposed by illness (Miller, Recsky & Armstrong, 2004), and consequently more attention has been directed to the assessment of positive dimensions of adaptation, such as happiness or wellbeing (Barlow & Ellard, 2006). Some recent work points out that children with chronic conditions may have as much or even greater probability for placing themselves in risky situations (Miauton, Narring & Michaud, 2003), or engage in risk behaviours such as suicide attempts, alcohol, tobacco and marijuana consumption (Blum, Kelly & Ireland, 2001), than their healthy peers.…”
Section: Introductionmentioning
confidence: 99%
“…Istraživanja su pokazala da su osobe s invaliditetom ipak u većem riziku od opće populacije kada se govori o narušenom mentalnom zdravlju (6)(7)(8)(9)(10). Međutim, pitanje povezanosti stresa uvjetovanog invaliditetom i mentalnog zdravlja ostaje nedovoljno istraženo i slabo poznato.…”
Section: Diskriminacija Stres I Mentalno Zdravljeunclassified